KONFLIK ANTARA WAHYU DAN AKAL DALAM HUKUM ISLAM - Kaddase, Thayyib (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
This paper is intended to describe the concept of role / function in the sense of revelation and understanding of Islamic law and the concept of conflict between revelation and reason in Islamic law based on Islamic values. This paper is a literature review that refers to the sources of Islam (the Quran and the Sunnah), using the deductive, inductive, and comparative. Then in the end with this paper can be seen that in order to understand the purpose / objective of Islamic law (sharia) sense has an important role to provide explanations on things that have not been explained by the revelation by the values of Islam (the Quran and Sunnah of Rasul saw).